A Briefing Survey on Advances of Coupled Networks With Various Patterns - Dong, Gaogao; Duan, Dongli; Xia, Yongxiang (Frontiers in Physics, 2021)
In real-world scenarios, networks do not exist in isolation but couple together in different ways including dependency relationships, multi-support, and inter-connection patterns. And, when a coupled network suffers from structural instability or dynamic perturbations, the system with different coupling patterns shows rich phase transition behaviors. In this review, we present coupled network models with different coupling patterns developed from real scenarios in recent years for studying the system robustness. For the coupled networks with different coupling patterns, based on the network percolation theory, this paper mainly describes the influence of coupling patterns on network robustness. In addition, for different coupling patterns, interdependence, multiple support attributes, and inter-connection, we show readers the research background, research context, and the latest research results. Furthermore, different approaches to improve system robustness for different coupling patterns and future possible research directions for coupled networks are explained ed and outlook.